Thiamin Deficiency in People with Obesity(1)(2) - Kerns, Jennifer C (Adv Nutr, 2015)
Although obesity has been viewed traditionally as a disease of excess nutrition, evidence suggests that it may also be a disease of malnutrition. Specifically, thiamin deficiency was found in 15.5–29% of obese patients seeking bariatric surgery. It can present with vague signs and symptoms and is often overlooked in patients without alcohol use disorders. This review explores the relatively new discovery of high rates of thiamin deficiency in certain populations of people with obesity, including the effects of thiamin deficiency and potential underlying mechanisms of deficiency in people with obesity. The 2 observational studies that examined the prevalence in preoperative bariatric surgery patients and gaps in our current knowledge (including the prevalence of thiamin deficiency in the general obese population and whether the current RDA for thiamin meets the metabolic needs of overweight or obese adults) are reviewed. Suggestions for future areas of research are included.